Large abscesses on the border of segment VII and VIII of the liver treated effectively pharmacologically – empirically chosen antibiotic therapy for a patient with diabetes - Malinowska, Marta; Kraśnicka-Sokół, Beata P.; Filczak, Krzysztof; Kochmański, Marek (Medical Studies/Studia Medyczne, 2015)
Liver abscesses are focal necroinflammatory lesions of bacterial, fungal, or amoebic origin. Pharmacological treatment is rarely sufficient if negative blood cultures are present. The report presents the case of a 62-year-old man with hypertension and type 2 diabetes, diagnosed with liver abscesses. The patient received two-stage empirical antibiotic therapy. Firstly in the hospital setting – cefuroxym, gentamicin, and metronidazole. After a 10-fold reduction in C-reactive protein and clinical improvement the patient was discharged home. In the second stage – ceftibutyn, metronidazole, and fluconasol were used in the outpatient setting. During rehospitalisation, a significant reduction in the size of abscesses was noted. The patient was twice consulted bacteriologically (treatment was accepted) and his computed tomography (CT) scans were sent for surgical consultation, which confirmed the effectiveness of the drug treatment and did not qualify for surgical treatment. In the 8-month follow-up there was no relapse and CT scans showed only scarring of the liver.